The effect of antimony presence in anodic copper on kinetics and mechanism of anodic dissolution and cathodic deposition of copper - Stanković Z.D.; Cvetkovski V.; Vuković M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The influence of the presence of Sb atoms, as foreign metal atoms in anode copper, on kinetics, and, on the mechanism of anodic dissolution and cathodic deposition of copper in acidic sulfate solution has been investigated. The galvanostatic single-pulse method has been used. Results indicate that presence of Sb atoms in anode copper increase the exchange current density as determined from the Tafel analysis of the electrode reaction. It is attributed to the increase of the crystal lattice parameter determined from XRD analysis of the electrode material.